DAMPAK KENAIKAN TARIF PAJAK PERTAMBAHAN NILAI (PPN) PADA MASYARAKAT DI INDONESIA - Helmalia Putri; Putu Siti Firmani; Luh De Liska; Ni Luh Putu Cahayani (Arthaniti Studies, 2026)
Taxes are due or mandatory contributions paid by the people or taxpayers to the state without directly receiving compensation that are used to improve government and public prosperity. In Indonesia, there are many types of taxes, one of which is VAT (Value Added Tax). PPN is a government levy imposed on every transaction of buying and selling goods and services carried out by individual taxpayers or corporate taxpayers who have become Taxable Entrepreneurs (PKP). The VAT rate increased to 11% from the previous 10%. This article aims to find out the impact of the increase in VAT rates for the community. This research uses a type of qualitative research. Data validity is obtained by searching for information from various sources. The result of this study is that although the VAT rate is very risky, the increase in the VAT rate will not interfere with the economic recovery process, because basic needs, education, health and social services are still not subject to VAT.